Perioperative Myocardial Injury After Noncardiac Surgery: Incidence, Mortality, and Characterization. Issue 12 (20th March 2018) - Puelacher, Christian; Lurati Buse, Giovanna; Seeberger, Daniela; Sazgary, Lorraine; Marbot, Stella; Lampart, Andreas; Espinola, Jaqueline; Kindler, Christoph; Hammerer, Angelika; Seeberger, Esther; Strebel, Ivo; Wildi, Karin; et al.
Abstract : Background: Perioperative myocardial injury (PMI) seems to be a contributor to mortality after noncardiac surgery. Because the vast majority of PMIs are asymptomatic, PMI usually is missed in the absence of systematic screening. Methods: We performed a prospective diagnostic study enrolling consecutive patients undergoing noncardiac surgery who had a planned postoperative stay of ≥24 hours and were considered at increased cardiovascular risk. All patients received a systematic screening using serial measurements of high-sensitivity cardiac troponin T in clinical routine. PMI was defined as an absolute high-sensitivity cardiac troponin T increase of ≥14 ng/L from preoperative to postoperative measurements. Furthermore, mortality was compared among patients with PMI not fulfilling additional criteria (ischemic symptoms, new ECG changes, or imaging evidence of loss of viable myocardium) required for the diagnosis of spontaneous acute myocardial infarction versus those that did. Results: From 2014 to 2015 we included 2018 consecutive patients undergoing 2546 surgeries. Patients had a median age of 74 years and 42% were women. PMI occurred after 397 of 2546 surgeries (16%; 95% confidence interval, 14%–17%) and was accompanied by typical chest pain in 24 of 397 patients (6%) and any ischemic symptoms in 72 of 397 (18%). Crude 30-day mortality was 8.9% (95% confidence interval [CI], 5.7–12.0) in patients with PMI versus 1.5% (95% CI, 0.9–2.0) in patients without PMI ( P <0.001). Multivariable regression analysis showed an adjusted hazard ratio of 2.7 (95% CI, 1.5–4.8) for 30-day mortality. The difference was retained at 1 year with mortality rates of 22.5% (95% CI, 17.6–27.4) versus 9.3% (95% CI, 7.9–10.7). Thirty-day mortality was comparable among patients with PMI not fulfilling any other of the additional criteria required for spontaneous acute myocardial infarction (280/397, 71%) versus those with at least 1 additional criterion (10.4%; 95% CI, 6.7–15.7, versus 8.7%; 95% CI, 4.2–16.7; P =0.684). Conclusions: PMI is a common complication after noncardiac surgery and, despite early detection during routine clinical screening, is associated with substantial short- and long-term mortality. Mortality seems comparable in patients with PMI not fulfilling any other of the additional criteria required for spontaneous acute myocardial infarction versus those patients who do. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02573532. Abstract : Supplemental Digital Content is available in the text.